Malignant peritoneal mesothelioma : Quantitative analysis of asbestos burden - Kurimoto, Ryota; Kishimoto, Takashi; Nagai, Yuichiro; Takazawa, Hiroshi; Sakaue, Nobuyuki; Shinohara, Yasushi; Hiroshima, Kenzo (Pathology international, 2009)
Malignant mesotheliomas develop commonly in the pleural cavity and rarely arise in the peritoneal cavity. It is well established that asbestos exposure is related to malignant pleural mesothelioma, but the asbestos burden in the abdominal cavity in patients with malignant peritoneal mesothelioma has not been well studied. The purpose of the present study was therefore to report on an autopsy case of malignant peritoneal mesothelioma with quantitative analysis of the asbestos burden in tissues from the pleura and organs in the abdominal cavity. The patient was a 67‐year‐old man with a history of asbestos exposure. The peritoneum was thickened with diffuse tumor proliferation. This patient was diagnosed as having malignant peritoneal epithelioid mesothelioma. The number of asbestos fibers was >10 000/g dry tissue in all samples examined except in the small intestine. The number of asbestos fibers in the stomach was 53 000/g, which was higher than that in a control asbestosis subject. The existence of numerous asbestos fibers found in the abdominal cavity suggests that asbestos stimuli are related to the tumorigenesis of malignant peritoneal mesothelioma.